The freelancer's bible - Horowitz, Sara.; Poynter, Toni Sciarra (New York : Workman Publishing, 2012)
Amazingly, one-third of the American workforce is freelance--that's 42 million people. Written by the authority on freelance working, Horowitz, MacArthur "Genius" Fellow and founder of the national Freelancers Union, creates a guide to help those new to freelancing.
Getting started.--Seven start-up steps.--Your office setup.--Your freelance portfolio.--Getting work.--Getting clients.--Closing the deal.--Clients 360°.--Troubleshooting.--Growing your business.--Marketing you.--Marketing yourself online.--Moving your freelancing to the next level.--The nimble freelancer: subcontracting and building teams.--Community : where personal and professional meet.--Managing your business.--Managing you.--Managing your office.--Taking care of taxes.--Your business and your community.--Working, playing, and staying on top of your game.--Your safety nets.
Includes index.
Keywords: SELF-EMPLOYED.; SUPPLEMENTARY EMPLOYMENT